Identity Politics and Local Regulations: A Critique of Ideology on Local Regulations in the Post-New Order - Eko Mukminto; Rofi Wahanisa (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
This article aims to study the identity politics embedded in local regulations in post-New Order Indonesia. This study used Critical Discourse Analysis to uncover the configuration of identity politics embodied in law and local regulations. After the fall of the New Order regime, the Indonesian government chose decentralization of power, which led to a path to regional autonomy. In its dynamics, several regional policies and regulations tend to project local legal politics with primordialism and conservativism in forming social coherence. Many regulations were criticized because it tends to have a complex nuance for minorities. From the analysis of several regional regulations or policies, the most prominent trend was Islamic identity. This study showed that Islamic identity became popularized and intertwined with local populism because New Order's centralism repressed Islam in the political landscape. Thus, after the fall of the new order regime, decentralization becomes a channel to offer the repressed ideological fantasy of Islamic legality at an elevated level.